OPTIMISING PRODUCTION EFFICIENCY THROUGH LEAN MANAGEMENT IN MANUFACTURING INDUSTRY - Lite Lite; Mahrawati; Robert Fransiska (ADISAM Publisher, 2025)
The application of Lean Management in the manufacturing industry is an effective strategy to improve production efficiency by reducing waste, improving quality, and speeding up production time. In this context, Lean Management focuses on eliminating non-value-adding activities and encourages flexibility and adaptability to changing market demands. The application of this methodology not only cuts operational costs, but also fosters a culture of collaboration and continuous improvement within the company. However, the success of Lean Management is highly dependent on the commitment of top management and the active participation of all employees in facing the challenges of organisational change. With the support of effective communication and strong leadership, manufacturing organisations can maximise the benefits of Lean Management and increase their competitive advantage in the global market.